Thyroid autoimmunity and function among Ugandan children and adolescents with type-1 diabetes mellitus - Muhame, Rugambwa Michael; Arwanire Mworozi, Edison; McAssey, Karen; Lubega, Irene (The Pan African Medical Journal, 2014)
Up to 30% of type-1 diabetes mellitus (T1DM) patients have co-existent thyroid autoimmunity with up to 50% of them having associated thyroid dysfunction. Routine screening for thyroid autoimmunity and dysfunction is recommended in all T1DM patients. However, this was not currently practiced in Ugandan paediatric diabetes clinics. There was also paucity of data regarding thyroid autoimmunity and dysfunction in African children and adolescents with diabetes mellitus. The objective of this study was to quantify the magnitude of thyroid autoimmunity and dysfunction in Ugandan children with TIDM. Methods: This was a cross sectional descriptive study to determine the prevalence of thyroid autoantibodies and describe thyroid function among children and adolescents aged 1-19 years with diabetes mellitus attending the paediatric diabetes clinic at Mulago National Referral Hospital, Kampala, Uganda. Following enrollment, we obtained details of clinical history and performed physical examination. Blood (plasma) was assayed to determine levels of antibodies to thyroid peroxidase (antiTPO), free thyroxine (FT4) and thyrotropin (TSH). Results: The prevalence of thyroid autoimmunity was 7.3% (5/69). All antiTPO positive subjects were post pubertal, aged between 13-17 years with females comprising 3/5 of the antiTPO positive subjects. All study subjects were clinically euthyroid; however, 7.3% (5/69) of the study subjects had subclinical hypothyroidism. Conclusion: These data strengthen the argument for routine screening of all diabetic children and adolescents for thyroid autoimmunity (particularly anti-TPO) as recommended by international guidelines. We also recommend evaluation of thyroid function in diabetic children and adolescents to minimize the risk of undiagnosed thyroid dysfunction.
Keywords: Thyroid; Autoimmunity; Type 1 diabetes mellitus; Children